Self-government of doctors in the context of their professional responsibility: economic, managerial, and legal aspects - Piekut, Marlena; Pacian, Jolanta Agnieszka (Medical Studies/Studia Medyczne, 2023)
Doctors have a duty to provide trustworthy and ethical medical care, and professional self-governments, such as chambers of physicians, play a crucial role in ensuring this responsibility. Economically, professional responsibility involves insurance costs, financial sanctions, increased healthcare expenses, and a decrease in patient trust. Managerially, it includes risk management, policy development, quality monitoring, and fostering a culture of safety. The self-government contributes by establishing standards, conducting inspections, and addressing complaints. Effective management of professional responsibility is essential for providing safe and high-quality healthcare. Mandatory membership in the self-government is determined by the supervision it exercises, ensuring that all practitioners are subject to oversight and comply with professional ethics. The self-government operates independently within its defined legal tasks. The article explores the organization and the role of professional self-government of doctors in upholding their professional responsibility. It examines economic, managerial, and legal aspects, addressing questions about monitoring professional practice, mandatory membership, ethical formulation, autonomy vs. state authority, and the connection between self-government and professional responsibility. The economic, managerial, and legal aspects emphasized underscore the significance of a well-functioning self-government system for the benefit of doctors and society at large. Brief description of the state of knowledge. The review was based on data obtained from articles published in research databases and law documents.